Phytochemical and phytotoxic investigation of the aqueous leaf extract of Eugenia dysenterica DC. under laboratory conditions - Malheiros, Rafael Pozzi; Mapeli, Ana Maria; Machado, Luciana Lucas (Ciência e Natura, 2018)
The objective of this study was to carry out a phytochemical characterization of the aqueous leaf extract of Eugenia dysenterica DC., as well as to evaluate its phytotoxic potential on the germination and growth of Lactuca sativa L. and Zea mays L. under laboratory conditions. Concentrations of 250, 500, 1000, 2000 and 4000 mg/L of the extract in addition to the control were used for the bioassays. Under laboratory conditions this extract inhibited average growth of the radicle/primary root and hypocotyl/coleoptile leaves of lettuce and maize, with proportionality between the effect and the concentration being observed. The presence of phenols, hydrolysable tannins, flavonols, flavanones, flavanonols, xanthones, flavones, free steroids and saponins were identifiedin the aqueous extract. The aqueous extract of the plant species under study has a phytotoxic effect, and this effect is due to the presence of phenolic compounds, tannins, flavonoids and saponins.